Natural freeze-thaw cycles may increase the risk associated with Salmonella contamination in surface and groundwater environments - Rocard, J.M. (2021)
We investigated the influence of temperature fluctuations around the freezing point, known as freeze-thaw (FT), on the inactivation rates, growth, and biofilm formation of a manure-isolated strain of Salmonella typhimurium. Moreover, the effects of FT on the transport characteristics of S. typhimurium in quartz sand were monitored in model porewater solutions of two different ionic strengths (IS: 10 and 100 mM KCl) and two different humic acid (HA) concentrations (1 and 5 mg/L). Increasing numbers of FT cycles were found to decrease the deposition of S. typhimurium onto quartz sand and increase the percentage of detached cells in sand-packed column experiments. Based on the calculated bacterial attachment efficiencies, the predicted minimum setback distances between the location of water supply wells and manure spreading activities are higher when the effects of FT are taken into consideration. While FT treatment significantly affected cell viability (in the presence of HA), most cells were in a viable but non-culturable (VBNC) state with compromised ability to form biofilm. This investigation demonstrates the effects of spring temperature variations in upper soil layers on S. typhimurium properties and the potential increased risk of bacterial contamination in representative aquifer environments in cold climate regions.